การพัฒนาฝีมือแรงงานที่ต้องการเพื่อเตรียมพร้อมเข้าสู่ประชาคมเศรษฐกิจอาเซียน: กรณีศึกษาสถานประกอบการใน 14 จังหวัดภาคใต้ - นกน้อย, เจษฎา; บริพันธ์, วรรณภรณ์ (Ratchaphruek Journal, 2016)
การวิจัยนี้มีวัตถุประสงค์เพื่อเปรียบเทียบการพัฒนาฝีมือแรงงานที่ผู้ประกอบการต้องการเพื่อเตรียมพร้อมเข้าสู่ประชาคมเศรษฐกิจอาเซียน จำแนกตามปัจจัย ส่วนบุคคลและปัจจัยด้านการดำเนินกิจการ กลุ่มตัวอย่าง คือผู้ประกอบการที่ได้รับอนุญาตให้ประกอบกิจการ ตาม พ.ร.บ. โรงงาน พ.ศ. 2535 ใน 14 จังหวัดภาคใต้ จำนวน 1,141 คน เครื่องมือที่ใช้ในการเก็บรวบรวมข้อมูลคือ แบบสอบถาม สถิติที่ใช้ในการวิเคราะห์ข้อมูลคือ ค่าความถี่ ค่าร้อยละ ค่าเฉลี่ย ส่วนเบี่ยงเบนมาตรฐาน และค่าความแปรปรวน (Analysis of Variance - ANOVA) ผลการวิจัยพบว่า ลักษณะและรูปแบบการฝึกอบรมที่ผู้ประกอบการต้องการมาก คือ การฝึกอบรมผู้บริหารระดับสูง การฝึกอบรมหัวหน้างาน การฝึกอบรมพนักงานใหม่ก่อนเข้าทำงาน และการฝึกอบรมพนักงานเดิมหลังทำงานมาแล้วระยะเวลาหนึ่งเพื่อเพิ่มพูนความรู้ ทักษะ ความชำนาญงาน การทดสอบสมมติฐานพบว่า การพัฒนาฝีมือแรงงานที่ผู้ประกอบการต้องการแตกต่างกันตามเพศ ระดับการศึกษา ประเภทของกิจการ ที่ตั้งของกิจการ ระยะเวลาในการดำเนินกิจการ และผลประกอบการ Skilled Labor Development Required When Preparing for Asean Economic Community (AEC) Entry: The Case of Enterprises in 14 Southern Thai Provinces This research aims to compare the workforce skill development required by various entrepreneurs to prepare for ASEAN Economic Community (AEC) entry and to classify them according to personal and operational factors. The research sample involved 1,141 entrepreneurs from 14 southern provinces in Thailand, all of which were permitted to operate enterprises according to the 1992 Factory Act. Questionnaires were used to collect, and frequency, percentage, mean, standard deviation, and analysis of variance were used to analyze the data. The results revealed that the training types that the entrepreneurs required at a high level were executive training, supervisor training, new employee training, and training long-standing employees to enhance their knowledge, skills and abilities. Research hypothesis found that the skill development required from entrepreneurs did vary by gender, education, type of enterprises, enterprise location, the duration of the operation, and earnings.